Kris Martin : idiot. - Martin, Kris; Dostoyevsky, Fyodor (Aspen, CO : Aspen Art Press, 2009)
Each new work by Belgian artist Kris Martin puts a fresh spin on the roles of process and duration in art. In this artist's book, Martin has written out the entirety of Fyodor Dostoyevsky's The Idiot, substituting his own name for that of the book's hero, Myshkin, in an extreme act of adulation and identification with Myshkin's desire for spiritual transformation.
boek
Keywords: Martin, Kris